Home medication management and practices among post-stroke patients: a cross-sectional study in a university-based primary care clinic in Malaysia - Nordin MHA,; Mohd Fairuz Ali,; Mohamed IN,; Bakry MM,; Aziz NA, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Effective medication management practice (MMP) improves compliance of chronic conditions management and reduces medication error for better clinical outcomes. This is important for stroke survivors with multiple comorbidities and post-stroke complications. This study aimed to determine appropriateness of home MMP and its associated factors among post stroke patients. This was a cross-sectional, single-centre study involving 120 stroke patients of a primary care medical centre in Kuala Lumpur between January and March 2021. The assessment of MMP appropriateness relied on scores obtained through a set of questions administered via face-to-face, online or telephone interview. The mean age of participants was 65.1 (SD 11.7) years. 55.8% of participants had inappropriate home MMP; where the majority did not update their medication list (86.3%), did not memorise the medication’s name (75%), and did not return the leftover medication to the pharmacy (63.3%). Female gender (AOR: 2.74, 95% CI: 1.18-6.35, p-value: 0.019), household income (> RM4850) (AOR: 2.82, 95% CI: 1.03-7.69, p-value: 0.043), and number of clinic appointments (>2) (AOR: 5.27, 95% CI: 1.44-19.24, p-value: 0.012) were significantly correlated with better home MMP. The MMP among post-stroke patients was poor. Better home MMP were associated with female gender, higher socioeconomic status, and more frequent clinic appointments. Concerted health education should be provided, particularly focusing on medication management to improve home MMP in post-stroke patients and ultimately improving their overall health outcomes.